Unconventional oil and gas: Global consequences - Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2013)
The United States is bucking the global energy trend, with a real prospect of becoming largely independent of fossil fuel imports, while major European consumers, China and India are preparing for increasing dependency. The global energy landscape is changing rapidly and profoundly, with trade flows shifting and security of supply issues re-shaping. At the same time, national energy paths increasingly diverge even within the OECD. Access to unconventional energy gives the United States a global competitive advantage, with far-reaching repercussions for economic and geopolitical structures. Russia – once an indispensable energy power – and the OPEC producers must adapt to a new market situation and enormous uncertainties about how the new world map for energy will fit together.
Keywords: 320